Rancang Model Ontologi Dalam Representasi Digital Loloh Cemcem Penglipuran - Putu Chandra Mayoni (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Bali is renowned for its diverse cultural heritage, including traditional herbal drinks like Loloh Cemcem from Penglipuran Village. This immunity-boosting beverage dates back to the Majapahit era but gained popularity during the COVID 19 pandemic. Despite being recorded as a Communal Intellectual Property, information about Loloh Cemcem is not well-structured, hindering knowledge dissemination. This research aims to address this issue by designing an ontology model to represent knowledge about Loloh Cemcem digitally. The Methodology approach is employed, consisting of specifying, knowledge acquisition, conceptualization, integration, implementation using Protégé software, evaluation through SPARQL queries, and documentation. The ontology model captures concepts, properties, relationships, and individuals related to Loloh Cemcem, facilitating structured information access and preservation of this traditional beverage’s knowledge.